Religijna materialność świata w powieści Grace McCleen „Świat Judyty” ” [„The Land of Decoration”] - Kowalcze, Małgorzata (Przestrzenie Teorii, 2023)
The article discusses the novel The Land of Decoration by Grace McCleen’s applying elements of selected posthumanist theories, mainly object-oriented ontology (G. Harman, T. Morton) and new materialism (J. Bennett). It considers the assumption that in the novel, the ontological status of human beings as well as material objects is fluid, as both play the role of a prop and the entity manipulating the prop. The author focuses on the main character’s religious cognitive perspective and her relations with her (im)material surroundings. An attempt is made to point out certain similarities between the religious worldview and the posthumanist approach. To this end, the author discusses several issues related to the dualistic categories of material vs. immaterial, rational vs. irrational, as well as human vs. non-human.